Unusual pathologic lesions in a heifer affected by Trueperella pyogenes - Lázaro, Fermín (2023)
Four Hereford heifers of approximately 18 months of age presented nodular formations in the uterus detected by transrectal palpation. This pathology had been previously diagnosed in the herd, which led to the early discarding of 1-2% of heifers per year. Post mortem examination in a severely affected heifer revealed multiple abscesses in the pelvic and abdominal cavity associated with the uterus, serosa of the forelimbs, and liver. Microscopically, the abscesses were characterized by a necrotic center with viable and degenerated neutrophils and necrotic debris, surrounded by a well-defined wall of connective tissue. In addition, multifocal neutrophilic ruminitis associated with acidosis was observed. Intralesional gram-positive bacilli were detected in the abscesses. Trueperella pyogenes was isolated from the purulent content. It is assumed that rumen acidosis was the origin of the dissemination and abscess formation of T. pyogenes in various tissues, including the uterus.